Perceptions of supply chain professionals on the relationship between supply chain challenges and business performance in the food industry in Gauteng province - Nguegan Nguegan, Catherine Angelique (Vaal University of Technology, 2017)
Effective supply chain management is largely contributing to the success of many companies around the world. From publicly owned companies to sole proprietorships, supply chain management is crucial in facilitating the effectiveness of all operations. In the food processing industry, supply chain management is regarded as important capital for both inbound and outbound logistical activities. However, implementation of supply chain management initiatives presents several challenges that hinder the effectiveness of the operations of most companies. The aim of this study was to investigate supply chain management challenges facing the food processing industry in South Africa and the effects of these challenges on business performance. Through a review of literature, seven challenges are identified, namely, human resources management, technology, facilities, supplier relationship management, customer relationship management, regulatory factors, logistics and transportation. A nine-section questionnaire was then developed using adapted measurement scales and distributed to 303 supply management professionals in food processing companies in Gauteng province. Respondents were selected using the non-probability convenience sampling technique. The collected data were analysed using the Statistical Packages for the Social Sciences (Version 23.0). After testing for validity and reliability, descriptive statistics were applied in testing perceptions of respondents towards the seven supply chain management challenges and business performance. Pearson correlations were used to test for the strength and direction of associations between supply chain management challenges and business performance. Regression analysis is applied in testing whether supply chain management predicted business performance. Application of Pearson correlations revealed negative associations between all seven supply chain management challenges and business performance. This implies that business performance decreases as the intensity of the challenges increases. Regression analysis indicated that, apart from regulatory factors, six of the supply chain management challenges predict business performance. Technology emerged as the strongest predictor of business performance. The study concludes by suggesting recommendations for limiting the impact of the identified challenges on business performance.
M.Tech (Logistics: Faculty of Management Sciences) Vaal University of Technology
Keywords: Supply chain professionals; Supply chain challenges; Business performance; Food industry; Business logistics; Dissertations Academic South Africa